Ways to Effectively Use Marketing Strategies to Increase the Customer Satisfaction of Physical Education and Sports Services - Dildora Jamalovna, Jalolova; Bahodir Asatillaevich, Abbosov; Zokir Abdurakhmonovich, Nazarov; Farrukh Akramjanovich, Mavlyanov; Dilafruz Abidovna, Khudayberdieva (International Journal of Psychosocial Rehabilitation, 2020)
It is known that the service sector is a common activity, and developed countries are the most important source of income that forms the gross domestic product. And also, the more developed the service sector, the more likely it is that the health of users is such. This also means the level of profitability of the country’s population. The article deals with issues related to the impact of the development of the service sector on the well-being of the population on a global scale.